2019
DOI: 10.1109/access.2019.2893538
|View full text |Cite
|
Sign up to set email alerts
|

2D Logistic-Modulated-Sine-Coupling-Logistic Chaotic Map for Image Encryption

Abstract: Due to the significant properties of unpredictability, ergodicity, and initial state sensitivity, chaotic system is widely used as a useful tool in image encryption. In this paper, we propose a 2-dimensional logistic-modulated-sine-coupling-logistic chaotic map (LSMCL), where we use the logistic map to modulate Sine map and couple the result of modulation and Sine map together. In terms of chaotic trajectory, Lyapunov exponent, and Kolmogorov entropy, comparing with other existing chaotic maps, we can observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 41 publications
(62 reference statements)
0
90
0
Order By: Relevance
“…The circle symbol in Equation 4represents the composition of two functions. Compared to the 1D delay and linearly coupled logistic chaotic map (DLCL) [15] and a two-dimensional logistic-modulated sine-coupling logistic chaotic map (LSMCL) [1], the structure of TDSCL produces better chaotic performance. In the following section, we use the trajectory, Lyapunov exponent, and permutation entropy (PE) to analyze the characteristics of chaotic maps.…”
Section: The Structure Of Chaotic Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…The circle symbol in Equation 4represents the composition of two functions. Compared to the 1D delay and linearly coupled logistic chaotic map (DLCL) [15] and a two-dimensional logistic-modulated sine-coupling logistic chaotic map (LSMCL) [1], the structure of TDSCL produces better chaotic performance. In the following section, we use the trajectory, Lyapunov exponent, and permutation entropy (PE) to analyze the characteristics of chaotic maps.…”
Section: The Structure Of Chaotic Mapsmentioning
confidence: 99%
“…where C(i, j) and C'(i, j) are the cipher image generated by the original key and the changed key in the key sensitivity test, respectively. The ideal values of NPCR and UACI are 99.6094% and 33.4635% for an 8-bit grey scale image, respectively [1]. Table 2 lists the simulation results.…”
Section: Key Sensitivity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…When the parameter r do not belong to this range, it cannot be considered to have a chaotic behavior and non-uniform distribution of the output chaotic sequences that affected the distributions of encrypted image data and the performance of encryption system. The Lyapunov exponent (LE) represents a quantitative measure of the sensitivity of the control parameters of chaotic maps [20]. Mathematically it can be represented as:…”
Section: Bifurcation Diagrammentioning
confidence: 99%
“…Chaotic maps with weak chaotic behaviors can make the cryptosystems vulnerable to attacks and can be easily broken. In recent years several works available in the literature have suggested to overcome the disadvantages of these chaotic maps by improving the properties of chaotic distribution for better performance and effectiveness of image encryption algorithms [19,20]. Hua et al [21] suggested a sine chaotic model (SCM) to improve the chaos complexity of existing chaotic range of (1-D) chaotic maps.…”
Section: Introductionmentioning
confidence: 99%